“A Sea of Troubles”: Oil Theft, Crude Economy and the Business of Organised Energy Crime in the Gulf of Guinea - Balogun, Wasiu A.; Adesanya, Olusegun Paul (African Journal of Stability and Development (AJSD), 2022)
The menace of oil theft in the Gulf of Guinea (GoG) has evolved into a ‘syndicated enterprise’ which mirrors underlying economic principles of formal business operations. The involvement of organised crime groups in primordial resource appropriation has altered dramatically the region’s energy landscape, accelerating a transition from an economy of greed to an economy of crime, underpinned by organised socio-economic structures which exploit the fragility of a manifestly troubled Gulf. The objective of this study flows from a resurgence in oil theft in the Niger Delta region, threatening energy-dependent economies like Nigeria and the wider Gulf of Guinea. The study submits that oil theft is an enterprise crime, and the resurgence of criminality particularly in Nigeria is a corollary of the entrenchment of organised crime in the region’s energy landscape and the availability of a flourishing crime environment in the Gulf of Guinea. The study concludes that oil theft poses a significant and growing threat to national and regional security, and combating criminality requires a cocktail of measures anchored on a robust appreciation of the nature of organised crime and the context within which it is nourished in the region.